An analysis of the state of cost management in India, with an emphasis on the role that supply chain applications play (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study encompasses fieldwork and academic considerations, including the comparison ofresearch methodologies, identification of research gaps, and selection of optimal research studies withinthe chosen topic. The literature review was conducted by analysing pertinent literature. The researcheremployed various academic databases including Ebsco, Google Scholar, Science Direct, ProQuest, andOATD. A comprehensive search was conducted on the topics of strategic cost management, moderncosting techniques, balanced scorecard, and small and medium-sized enterprises. In this study, anextensive examination was conducted on various sources including books, research papers, theses, andgovernment reports. The objective of this study is to analyse research conducted in India as well asresearch conducted globally. Strategic cost management for small and medium-sized enterprises (SMEs)is a crucial aspect of business operations. By implementing effective cost management strategies, SMEscan optimise their financial resources and enhance their overall profitability. This The process of costaccounting involves the allocation of expenses to the various operations of ABC. The method describedherein enhances decision-making and resource allocation by improving the accuracy of activity costestimation. The Balanced Scorecard (BSC) is a performance measurement framework that assesses theeffectiveness of strategic management. Benchmarking is a method used to assess systems, processes,and products by comparing them to established industry standards. The request is for Key PerformanceIndicators (KPIs) and statistical data. Cost-controllingThe implementation of Kaizen methodologiesresults in a reduction in costs, leading to a decrease in prices. The LCC (Life Cycle Cost) methodology isutilised to estimate the costs associated with a product or system throughout its entire life cycle. Thethree key stages in the life cycle of an asset are acquisition, maintenance, and disposal. TargetCorporation is a multinational retail corporation that engages in the sale and manufacturing of variousproducts.